Telemedicine : New Era of Health Service (Journal of Chittagong Medical College Teachers' Association, 2019)
Telemedicine has the potential to help facilitate the delivery of health services to rural and remote areas. In somecircumstances, telemedicine may also be useful for the delivery of education and teaching programmes and the facilitation of administrative meetings. In this paper reference is made to a variety of telemedicine applications. An overriding imperative is to focus on the clinical problem first with careful consideration given to the significant organisational changes which are associated with the introduction of a new or alternative method of health service delivery for remote patients. For telemedicine to be effective it is also important that all sites involved are adequately resourced in terms of staff, equipment, telecommunications, technical support and training. In addition, there are a number of logistical factors which are important when considering the development of a telemedicine service including site selection, clinician empowerment, telemedicine management, technological requirements, user training, telemedicine evaluation, and information sharing through publication.JCMCTA 2019 ; 30 (1) : 5-11